2003
DOI: 10.1289/ehp.5742
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transplacental exposure to environmental pollutants on birth outcomes in a multiethnic population.

Abstract: Inner-city, minority populations are high-risk groups for adverse birth outcomes and also are more likely to be exposed to environmental contaminants, including environmental tobacco smoke (ETS), polycyclic aromatic hydrocarbons (PAHs), and pesticides. In a sample of 263 nonsmoking African-American and Dominican women, we evaluated the effects on birth outcomes of prenatal exposure to airborne PAHs monitored during pregnancy by personal air sampling, along with ETS estimated by plasma cotinine, and an organoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
525
3
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 550 publications
(552 citation statements)
references
References 39 publications
20
525
3
4
Order By: Relevance
“…The study provides evidence that environmental contaminants at levels currently encountered in New York City adversely affect fetal development. (Perera et al, 2003) A more recent prospective epidemiological study in support of the deleterious effects of gestational exposure to PAH's on cognitive functioning was reported recently by Perera et al, (2006). An effect of prenatal exposure to airborne polycyclic aromatic hydrocarbons on neurodevelopment in the first 3-years of life among inner-city children was identified.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The study provides evidence that environmental contaminants at levels currently encountered in New York City adversely affect fetal development. (Perera et al, 2003) A more recent prospective epidemiological study in support of the deleterious effects of gestational exposure to PAH's on cognitive functioning was reported recently by Perera et al, (2006). An effect of prenatal exposure to airborne polycyclic aromatic hydrocarbons on neurodevelopment in the first 3-years of life among inner-city children was identified.…”
Section: Introductionmentioning
confidence: 89%
“…Epidemiological studies have shown that unintended gestational exposure of the fetus to environmental contaminants, such as B(a)P, adversely affects fetal development, results in low birth weight and reduced head circumference that manifests as neurobehavioral deficits such as poorer outcome on selective aspects of cognitive and neuromotor functioning in offspring (Hack et al, 199;Perera et al, 2003;Landrigan et al, 2004). For example, in a sample of 263 nonsmoking inner-city African-American and Dominican women, the effects of gestational exposure to airborne PAHs on birth outcomes was monitored during pregnancy by personal air sampling in New York City.…”
Section: Introductionmentioning
confidence: 99%
“…The literature indicates that chronic CPF exposure is associated with decreased birth weight and length. In addition, lower birth weights have specifically been documented among African Americans infants (Rauh et al 2006;Perera et al 2003) exposed to CPF in utero. Finally CPF exposure is associated with alterations in developmental and psychomotor indices in Mexican-American children (Eskenazi, et al 2007) and with immunological abnormalities (Thrasher et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies were devoted to the transmittance of EDC and assessing their content in the cord blood serum and maternal adipose tissue [13][14][15][16][17][18][19][20][21][22][23][24][25][26], showing that a fetus and once born an infant may be exposed to significantly high levels of EDC [27]. This can result in a decrease in fetal birth weight, premature birth, psychomotor retardation and altered cognitive function [28][29][30][31][32][33].…”
Section: Endocrine Disrupting Compoundsmentioning
confidence: 99%